The Spirit of the Learned Laws - Charles J. Reid Jr. (Washington University Global Studies Law Review, 2002)
In this book review, Charles J. Reid Jr. offers a review of Alan Waton's, The Spirit of Roman Law, and R.H. Helmholz's, The Spirit of Classical Canon Law.
Keywords: The Spirit of Roman Law; Alan Watson; The Spirit of Classical Canon Law; Helmholz; R. H.; Legal history